Synthesis of ceria based superhydrophobic coating on Ni20Cr substrate via cathodic electrodeposition. Issue 47 (12th November 2015) - Pedraza, F.; Mahadik, S. A.; Bouchaud, B.
Abstract : In this woks, we present designing strategy for superhydrophobic ceria coating on a Ni20Cr substrate is obtained by combination of electropolishing process, cathodic electrodeposition and subsequent long-term UVH surface relaxation. Abstract : In this work, superhydrophobic cerium oxide coating surface (111) with dual scale texture on Ni20Cr substrate is obtained by combination of electropolishing the substrate and subsequent cathodic electrodeposition and long-term UVH surface relaxation. To form hierarchical structures of CeO2 is controllable by varying the substrate roughness, and electropolishing period. The results indicated that at the optimal condition, the surface of the cerium oxide coating showed a superhydrophobicity with a great water contact angle (151.0 ± 1.4°) with Gecko state. An interface model for electropolishing of substrate surface in cerium nitrate medium is proposed. We expect that this facile process can be readily and widely adopted for the design of superhydrophobic coating on engineering materials.